Neoaustin: a meroterpene produced by Penicillium sp. - Zukerman-Schpector, Julio; Maganhi, Stella H.; Fill, Taicia Pacheco; Rodrigues-Fo, Edson; Caracelli, Ignez [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The title meroterpene neoaustin {systematic name: (1'S,2'R,3S,7'R,9'S,11'S,12'R)-11'-hydroxy- 2,2,2',9',12'-pentamethyl-6',15'-dimethylene-2,6-dihydro-13'-oxaspiro[pyran-3,5'-tetracyclo[7.5.1.0(1,11).0(2,7)]pentadecane]-6,10',14'-trione}, C(25)H(30)O(6), comprises five rings, three six-membered and two five-membered. The absolute configuration was established based on [alpha D] = + 166.91 degrees (c 1.21, CH(2)Cl(2)). In the crystal, the molecules are connected into a supramolecular helical chain via O-H center dot center dot center dot O hydrogen bonds reinforced by C-H center dot center dot center dot O contacts.